Developments in organic solid-liquid phase change materials and their applications in thermal energy storage - Sharma, R.K.; Ganesan, Poo Balan; Tyagi, V.V.; Metselaar, H.S.C.; Sandaran, S.C. (Elsevier, 2015)
Thermal energy storage as sensible or latent heat is an efficient way to conserve the waste heat and excess energy available such as solar radiation. Storage of latent heat using organic phase change materials (PCMs) offers greater energy storage density over a marginal melting and freezing temperature difference in comparison to inorganic materials. These favorable characteristics of organic PCMs make them suitable in a wide range of applications. These materials and their eutectic mixtures have been successfully tested and implemented in many domestic and commercial applications such as, building, electronic devices, refrigeration and air-conditioning, solar air/water heating, textiles, automobiles, food, and space industries. This review focuses on three aspects: the materials, encapsulation and applications of organic PCMs, and provides an insight on the recent developments in applications of these materials. Organic PCMs have inherent characteristic of low thermal conductivity (0.15-0.35 W/m K), hence, a larger surface area is required to enhance the heat transfer rate. Therefore, attention is also given to the thermal conductivity enhancement of the materials, which helps to keep the area of the system to a minimum. Besides, various available techniques for material characterization have also been discussed. It has been found that a wide range of the applications of organic PCMs in buildings and other low and medium temperature solar energy applications are in abundant use but these materials are not yet popular among space applications and virtual data storage media. In addition, it has also been observed that because of the low melting point of organic PCMs, they have not yet been explored for high temperature applications such as in power plants. (C) 2015 Elsevier Ltd. All rights reserved.